2009
DOI: 10.2214/ajr.08.2161
|View full text |Cite
|
Sign up to set email alerts
|

History of Uterine Artery Occlusion and Subsequent Pregnancy

Abstract: In the long run, placental abnormalities may be the canary in the mine shaft to globally judge the effect of uterine artery embolization on pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 122 publications
0
7
0
Order By: Relevance
“…Additionally, the influence of embolic material on the endometrium and uterine cavity has been postulated to adversely affect implantation and placentation. 23,24 Despite these concerns, none of them have been validated.…”
Section: Effects Of Embolization On Fertilitymentioning
confidence: 99%
“…Additionally, the influence of embolic material on the endometrium and uterine cavity has been postulated to adversely affect implantation and placentation. 23,24 Despite these concerns, none of them have been validated.…”
Section: Effects Of Embolization On Fertilitymentioning
confidence: 99%
“…This deep invasion of EVT into uterine muscle wall is specific to primates, making it difficult to model in rodents for experimental use. However, occlusion of uterine artery induces PE-like symptoms in rodents [66]. Using this model, it has been reported that Tregs are decreased in this model, and injection of Tregs improves the PE-like symptoms [67], suggesting that Tregs may be useful for the treatment of PE.…”
Section: Immune Abnormalities In Pementioning
confidence: 85%
“…the blood supply to the uterus were mentioned over 120 years ago. In 1894, Kelly presented the ligation of internal iliac arteries during an oncological hysterectomy to control intractable pelvic bleeding, which at that time was a common complication after the surgical procedure 28 . Then, Sack (1973) described the effective use of the same technique in the treatment of massive postpartum hemorrhage after forceps delivery.…”
Section: Methods Of Therapeutic Vascular Occlusion and Blockingmentioning
confidence: 99%